Korean Wave Issue as A Soft Power Strategy in Taiwanese Presidential Election 2016 - Raaf Bezkarannu; Ani Widyani Soetjipto (Insignia: Journal of International Relations, 2022)
AbstractBoth state and non-state actors need the power to influence others to achieve their desired goals. Soft power isoften used by state or non-state actors to attracts the attention of others without using coercive actions to achievethe desired goals. This strategy has been widely used in various cases, including in the issue of China and Taiwan,especially in the "Taiwan Flag" incident involving Tzuyu, a K-Pop artist who declared herself a Taiwanese andcarried the Taiwan flag on a South Korean television program. This incident was later brought up by Tsai Ingwen, a politician from Democratic Progressive Party (DPP) to cooperate with the Taiwanese people against Chinain the 2016 Taiwan Presidential Election. This article will discuss how Tsai Ing-wen and the people of Taiwan usedKorean wave as a soft power strategy in the 2016 Taiwan Presidential Election to “fight” against China. Thosegave positive results due to the similarity of political values believed by Taiwan and carried by the Korean wave,as well as the goals shared by Tsai Ing-wen and people of Taiwan, thereby defeated the pro-China Kuomintang(KMT) party in the election.Keywords: Soft Power, Taiwan, China, Korean Wave, Taiwan Presidential Election 2016, Taiwan Flag IncidentAbstrakBaik aktor negara maupun non-negara memerlukan kekuatan untuk mempengaruhi pihak lain agar tujuan yangdiinginkan dapat tercapai. Salah satunya adalah soft power yang mengedepankan upaya menarik perhatianpihak lain tanpa menggunakan tindakan koersif untuk mencapai tujuan yang diinginkan. Implementasi strategitersebut telah banyak dimanfaatkan dalam berbagai kasus, salah satunya dalam isu China dan Taiwan dalam the“Waving Taiwan Flag” incident yang melibatkan Tzuyu yang merupakan artis K-Pop yang mendeklarasikan dirisebagai warga negara Taiwan serta membawa bendera Taiwan dalam salah satu program televisi di KoreaSelatan. Insiden tersebut kemudian diangkat oleh Tsai Ing-wen, seorang politisi dari Democratic ProgressiveParty (DPP) untuk bekerja sama dengan masyarakat Taiwan untuk melawan China dalam Taiwan PresidentialElection 2016. Artikel ini membahas bagaimana Tsai Ing-wen dan masyarakat Taiwan memanfaatkan isu Koreanwave sebagai strategi soft power dalam Taiwan Presidential Election 2016 untuk “melawan” kampanye pro Chinayang disuarakan oleh KMT. Implementasi isu Korean wave sebagai strategi soft power dalam Taiwan PresidentialElection 2016 memberikan hasil positif dan ikut mempengaruhi kemenangan Tsai Ing-wen dalam pemilu diTaiwan di tahun 2016.Kata Kunci: Soft Power, Taiwan, China, Korean Wave, Pemilu Presiden Taiwan 2016, Insiden Bendera Taiwan